2013
DOI: 10.1021/es4016926
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated EV Adoption: Double-Digit Reductions in Emissions and Fuel Use for $40/Vehicle-Year

Abstract: Adoption of electric vehicles (EVs) would affect the costs and sources of electricity and the United States efficiency requirements for conventional vehicles (CVs). We model EV adoption scenarios in each of six regions of the Eastern Interconnection, containing 70% of the United States population. We develop electricity system optimization models at the multidecade, day-ahead, and hour-ahead time scales, incorporating spatial wind energy modeling, endogenous modeling of CV efficiencies, projections for EV effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 17 publications
(18 reference statements)
0
27
0
Order By: Relevance
“…The gap between correlation and causality is particularly evident for the dispatch of hydroelectric plants, which may change generation timing in response to new load but typically will not change total energy generated in response to new load. Alternatively, bottom-up normative models of the power system, such as those used by Sioshansi et al [9], Peterson et al [10], Choi et al [11] and Weis et al [12], use optimization models to estimate how a power system should operate to minimize costs subject to a variety of constraints. These models can assess changes of grid operation in response to new PEV load.…”
Section: Introductionmentioning
confidence: 99%
“…The gap between correlation and causality is particularly evident for the dispatch of hydroelectric plants, which may change generation timing in response to new load but typically will not change total energy generated in response to new load. Alternatively, bottom-up normative models of the power system, such as those used by Sioshansi et al [9], Peterson et al [10], Choi et al [11] and Weis et al [12], use optimization models to estimate how a power system should operate to minimize costs subject to a variety of constraints. These models can assess changes of grid operation in response to new PEV load.…”
Section: Introductionmentioning
confidence: 99%
“…Published studies (e.g., Choi et al 2013;Wang et al 2011;Druitt and Früh 2012) mainly refer to systems in which scheduling the recharging of EVs can help to smooth temporal variations in demand and thereby enable more use of intermittent renewable sources. Sternberg and Bardow (2015) concluded that, if storage is added to an existing grid, the highest GHG reductions are achieved by using surplus power in heat pumps and EVs.…”
Section: The Role Of Energy Storagementioning
confidence: 99%
“…Published studies (e.g., Choi et al. ; Wang et al. ; Druitt and Früh ) mainly refer to systems in which scheduling the recharging of EVs can help to smooth temporal variations in demand and thereby enable more use of intermittent renewable sources.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, equation 11 shows the objective function-minimizing the cost of electricity production over time, in this case from Choi et al [31]. Here Ci, Fi, and Vi are the capital costs, fixed operating costs, and variable operating costs of each type of electricity generation i for each year t; r is the discount rate.…”
Section: Least Cost Optimizationmentioning
confidence: 99%
“…The decision variables are the total capacity (in MW) of each generation technology in each time period, xi,t, the new capacity to be built in each time period, yi,t , the capacity to be retired, qi,t, and the amount of electricity to be generated for electric vehicles, zev i,s,w,h,t , and for all other uses, z i,s,w,h,t . This problem is designed to examine the interactions of wind energy generation and electric vehicles, so both of these activities are modeled separately: electricity generation is represented by zev and z for the electricity used for electric vehicles (EVs) and for all other demand, respectively, and LCwind is the levelized cost of wind energy and zwind is the electricity generated from wind resources at season s and hour h. Further details are given in Choi et al [31].…”
Section: Least Cost Optimizationmentioning
confidence: 99%